Distinguishing Between Multisystem Inflammatory Syndrome, Associated With COVID-19 in Children and the Kawasaki Disease: Development of Preliminary Criteria Based on the Data of the Retrospective Multicenter Cohort Study - Kostik, Mikhail M.; Bregel, Liudmila V.; Avrusin, Ilia S.; Dondurei, Elena A.; Matyunova, Alla E.; Efremova, Olesya S.; Isupova, Eugenia A.; Kornishina, Tatiana L.; Masalova, Vera V.; Snegireva, Ludmila S.; Shprakh, Vladimir V.; Kozlov, Yuri A.; et al. (Frontiers in Pediatrics, 2021)
Objectives Diagnostic between multisystem inflammatory syndrome associated with COVID-19 in children (MIS-C) and Kawasaki disease (KD) can make difficulties due to many similarities. Our study aimed to create a Kawasaki/MIS-C differentiation score (KMDscore) allowing discrimination MIS-C and KD. Study design: The retrospective multicenter cohort study included clinical, laboratory, and instrumental information about MIS-C (n=72) and KD (n=147). The variables allowed to discriminate both conditions used to construct and validate the diagnostic score called the KMDscore. Results: Patients with MIS-C were older and had earlier admission to the hospital, a shorter time before fever resolution, two times frequently had signs of GI and CNS involvement had been observed and, had more impressive thrombocytopenia, higher level of CRP, ferritin, ALT, AST, LDH, creatinine, triglycerides, troponin, D-dimer compared to KD patients. Respiratory signs in MIS-C were presented with pleuritis, acute respiratory distress syndrome, oxygen dependency, lung infiltration, ground-glass opacities in CT. The heart involvement with fast progression of myocarditis provided the severity of MIS-C and ICU admission due to 12 times higher arterial hypotension or shock and required cardiotonic. No differences in the frequency of CA lesions were seen in the majority of cases. Five criteria: CRP>11 mg/dl (18 points), D-dimer>607 ng/ml (27 points), age >5 years (30 points), thrombocytopenia (25 points), and GI involvement (28 points) were included in the KMDscore. The summa>55 points allowed to discriminate MIS-C from KD with a sensitivity of 87.5% and specificity of 89.1%. Conclusion: The KMDscore can be used to differential diagnostic of MIS-C from KD.